Infection of finger caused by Morganella morganii leading to digital amputation: A case report. Issue 2 (January 2019) - Li, Di; Gao, Wenshan; Niu, Yanan; Zhao, Pei; Zheng, Wenkui; Li, Cong Jie
Abstract: Rationale: Digital infection is a common disease in clinic, featured by pain and swelling of digits. As far as we know, no article has reported a case of digital infected by Morganella morganii . Patient concerns: A 58-year-old Chinese female complains about whitlow with pain and swelling for 2 weeks. She has a history of diabetes for 10 years. She received incision and drainage before coming to our hospital and preoperative X-ray of left ring finger presented no bone eroded. Diagnosis: She is diagnosed with infection of ring finger caused by M morganii in our hospital. Interventions: We perform aggressive operative debridement and drainage firstly. Meanwhile, we provide tissue samples for diagnosis and the result indicates M morganii infection. Then, she is treated with anti-infection therapy and regulation of diabetes. However, 1 week after first surgery, her condition deteriorate presenting bone erosion in distal phalanx of ring finger from X-ray. Considering severity of illness, we decide to perform digital amputation. Outcomes: At 3-month follow-up, the patient has a satisfactory result and X-ray shows no bone eroded. Lessons: Clinicians should consider M morganii, which is rare in hand infection, as a cause of digital infection. This case reminds us that some whitlow is dangerous, amputation should be considered if necessary.